Isolation and epidemiology of multidrug resistant Escherichia coli from goats in Coxs Bazar, Bangladesh - Islam, Kamrul; Ahad, Abdul; Barua, Mukti; Islam, Ariful; Chakma, Shovon; Dorji, Chendu; Uddin, Mohammed Arif; Islam, Shariful; Ahasan, A. S. M. Lutful (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The investigation was undertaken to measure the epidemiological features and antimicrobial sensitivity patterns of Escherichia coli among different breeds of goats in Coxs Bazar, Bangladesh. Materials and methods: A total of 150 rectal swab samples were collected from selected goats. The samples were subjected for the isolation of E. coli through a series of conventional bacteriological and biochemical techniques. The isolated E. coli were used for assessing antimicrobial susceptibility by disk diffusion method. Besides prevalence study, nine risk factors were studied; the risk factors were- breed, age, hygienic status, sex, history of recent transportation, season, diarrhea, body condition score, and source of drinking water. Results: The overall prevalence of E. coli in the rectal swabs of goats was 52% (n=78/150). The young goats were highly susceptible (65.0%; n=52/80) to E. coli infection as compared to adults (37.1%; n=26/70). The prevalence was higher (66.7%; n=42/63) in the goats that was reared in poor hygienic condition as compared to the goats that were reared under good hygienic condition. The influence of the source of drinking water on E. coli prevalence was found to be higher both in pond (63.6%; n=7/11) and municipality (61.4%; n=51/83) supplied water as compared to tube-well (35.7%; n=20/56). The goats having recent transportation history showed higher prevalence (64.8%; n=35/54). The prevalence was higher in diarrheic goats (62.0%; n=49/79) than non-diarrheic goats. Among the E. coli isolates (n=78), 31 were found to be multidrug resistant (MDR) to 3 to 8 subclasses of antimicrobials. Conclusion: Presence of MDR E. coli in the studied goats suggest the probable acquisition, development and transmission of MDR E. coli through a number of influencing factors to other animals and potentially to human. http://doi.org/10.5455/javar.2016.c147